Elements of Nature and Human Sensibility in Devkota’s Poem Make me a Sheep, O Lord - Poudel, T.N. (Medha: A Multidisciplinary Journal, 2023)
This article explores the elements of Nature and Human Sensibility in the poem ’Make me a Sheep, O Lord’ composed by Laximi Prasad Devkota in 1947 AD. He was impressed by British romantic poets, and is the pioneer of the Nepali Romanticism. So, it is suitable to study his poem in relation to the elements of romanticism. Nature is the key element of romanticism. The concept of human sensibility covers a range of ideas related to poet’s experiences, feelings, sentiments, emotions, views and subjectivity. It has dual links. Though it is a pre-romantic concept, it is widely found in the Romantic period too. The study makes an attempt to interpret the images, symbols, concepts, figure of speech etc. in the poem in relation to nature and human sensibility. The article follows romanticism as a theory of analysis. The study confirms the prevalence of elements of nature and human sensibility throughout the poem. Regarding the form and translation, the study is based on Pen Himalaya’s English version of the poem Prabhu ji Mlai Bhedo Banau. It has adopted the qualitative and impressionistic method of study. For the purpose of textual analysis, the writer of this article depends on works of research studies, journals and articles on the relevant subject. This paper can be utilized by and significant for readers, researchers, teachers and students.